Pendampingan Pastoral terhadap Anak yang Trauma Karena Bapaknya Meninggal - Hidayat F.H. Pasaribu; Rogate Artaida Tiarasi Gultom; Ibelala Gea (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
The experience of losing a parent has an impact on a child's life. When this event occurs, you will experience a feeling of loss which ultimately causes grief. In fact, this event had a physical, emotional and spiritual impact because of the child's grief over the death of his parents. Situations like this ultimately cause trauma to the person, therefore a healing process is needed for people who experience abnormal sadness. The purpose of this article is to describe a trauma-based approach to dealing with abnormal grief in adolescents whose parents have died. This research uses a qualitative literature method with a literature review using a content analysis approach. This study provides insight into the definition of pathological grief and trauma healing. Symptoms of excessive mourning experienced by adolescent children after the death of their parents. And knowledge about how to overcome grief using a trauma healing approach.